Muslim women and the new gods: psycho-sociological study on the influence of the media on women - Ramdane, Tahraoui; Souad, Merah (IIUM Press, 2009)
Introduction: When the term religion is mentioned, the classical and universal connotation often crosses the mind that is the correlated triplicity: The Holy, Believing in the Holy and the Application of those beliefs in a form of Rituals. However......